Visual perception and its effect on reaction time and time - movement anticipation in elite female basketball players - Mankowska, M.; Poliszczuk, T.; Poliszczuk, D.; Johne, M. (Polish Journal of Sport and Tourism, 2015)
The efficient collection and analysis of information from both the central and the peripheral field of vision may affect human coordination motor abilities. An analysis of the literature on the subject suggests that coordination motor abilities interact with one another, and it is only their combined effect that allows athletes to achieve technical mastery. The main aim of the study was to assess specific coordination motor abilities and to determine how visual perception and reaction time correlate with time-movement anticipation in elite female basketball players. Material and methods. The study participants comprised 17 female basketball players from the Polish National Team aged 18.1 ± 0.8 years. The study involved three ability tests from the Vienna Test System: the Reaction Test (RT, S1), the Peripheral Perception test (PP), and the Time/Movement Anticipation test (ZBA, S2). Results. The analysis of the results obtained proves that the best-developed ability in participants is reaction time, while the other abilities show average development. Study participants were able to develop their response abilities to such high levels by means of practice. A correlation coefficient was found between motor time and tracking deviation (r=0.56), and between time anticipation and the number of correct responses to stimuli appearing in the left (r=0.92) and right (r=0.88) field of vision. Athletes who achieved better results in time anticipation omitted fewer visual stimuli (r=0.7) in the peripheral field of vision. Statistically significant correlations were observed between movement anticipation and reaction time to stimuli in the central field of vision (r=0.58). Conclusions. Perception abilities have a significant effect on time anticipation. The range of one's field of vision does not determine the reaction time to a visual stimulus. Perception efficiency and divided attention, in conjunction with time and movement anticipation, create a complex of specific psychomotor abilities that is indispensable for achieving success in team sports.